Thermal decomposition kinetics of torrefied oil palm empty fruit bunch briquettes - Nyakuma, B. (Lviv Polytechnic National University, 2016)
The study is aimed at investigating the thermal behavior and decomposition kinetics of torrefied oil palm empty fruit bunches (OPEFB) briquettes using a thermogravimetric (TG) analysis and the Coats-Redfern model. The results revealed that thermal decomposition kinetics of OPEFB and torrefied OPEFB briquettes is significantly influenced by the severity of torrefaction temperature. Furthermore, the temperature profile characteristics; Tonset, Tpeak, and Tend increased consistently due to the thermal lag observed during TG analysis. In addition, the torrefied OPEFB briquettes were observed to possess superior thermal and kinetic properties over the untorrefied OPEFB briquettes. It can be inferred that torrefaction improves the fuel properties of pelletized OPEFB for potential utilization in bioenergy conversion systems.